Pattern of choroidal thickness in early-onset high myopia - Jiang, Zhaoxin; Hou, Aohan; Zhang, Ting; Lai, Yanting; Huang, Li; Ding, Xiaoyan (Frontiers in Medicine, 2023)
Purpose To explore the etiology and choroidal thickness (ChT) pattern in children with early-onset high myopia (eoHM). Methods Sixty children with eoHM and 20 healthy controls were enrolled in this study between January 2019 and December 2021. All children underwent comprehensive ophthalmologic examinations including swept-source optical coherence tomography. ChT was measured in the subfoveal region and at 1000 μm and 2,500 μm nasal, temporal, superior, and inferior to the fovea. Results Overall, 120 eyes of 60 children with eoHM were examined (mean spherical equivalent, −8.88 ± 3.05 D; mean axial length, 26.07 ± 1.59 mm). Simple high myopia (SHM), familial exudative vitreoretinopathy (FEVR), and Stickler syndrome (STL) were the most frequent etiologies of eoHM and were included in further ChT analysis. Adjusted the effect of SE, multivariate regression analysis showed that children with SHM had thinnest ChT at N2500 and I2500 among the subgroups (p = 0.039, p = 0.013). FEVR group showed thinner ChT at T2500 (p = 0.023), while STL patients exhibited thin ChT at all locations. Conclusion This study revealed that SHM, STL and FEVR was the most frequent etiology, and showed a distinctive pattern of ChT. Asymmetric nasal ChT thinning is a distinctive biomarker for SHM, asymmetric temporal ChT thinning might serve as a biomarker for FEVR, and symmetric diffuse thinning is more common in STL. These ChT patterns may provide a convenient, fast, and noninvasive strategy to differentiate the potential etiology of eoHM.